Relationship of selected conditioning parameters and sport performance indicators in karate - Nema, Kristina; Ruzbarsky, Pavel; Rydzik, Łukasz; Peric, Tomas (Frontiers in Sports and Active Living, 2024)
The variables of aerobic performance and aerobic capacity are of significant importance in maintaining intensity during a fight and also contribute to faster recovery between rounds in sports fighting in karate. Anaerobic performance is crucial for the execution of the techniques during high-intensity offensive or defensive actions that determine the outcome of a fight. The objective of this study was to assess the relationship between selected performance indicators of aerobic and anaerobic capacity to sports performance in karate. Methods: The study included six male karate athletes (age 28 ± 3 years, body mass 85.10 kg; height 185.5 cm), medalists from European and World championship, events in senior categories. The selection criteria included training experience and sports level. The Karate specific aerobic test (KSAT) was use in conjunction with heart rate monitoring and changes in blood lactate levels to diagnose special aerobic endurance parameters. To determine the level of anaerobic performance the Wingate test were choosed. Technical and tactical indicators (efficiency, effectiveness and activeness of the attack) were used to assess the sports skill level during competition. Results: Based on the Spearman correlation coefficient results demonstrated statistically significant differences (rs = -0.81)with large effect size index between efficiency of the attack and average heart rate achieved in the test KSAT. Additionally statistically significant differences (rs= 0.81) with large effect size were demonstrated between the fatigue index and efficiency of the attack Furthermore, the selected indicators of special aerobic endurance parameters and anaerobic performance demonstrated a high degree of predictive validity in relation to the efficiency (rp = 0.960) and activity (rp = 0.927) of attacks. Conclusion: The high level of predictive validity confirmed the importance of a high level of anaerobic conditions for performance in karate. The low values of the average heart rate in relation to the efficiency of the attack confirm the high performance level of karate athletes in relation to special aerobic performance parameters. It was found that the effectiveness of the attack had no relation to the monitored parameters.